A Simple Proof for a Theorem of Nagel and Schenzel - Huong, Duong Thi (VNU Journal of Science: Mathematics - Physics; Vol 33 No 4DO - 10.25073/2588-1124/vnumap.4249, 2017)
Nagel-Schenzel’s isomorphism that has many applications was proved by using spectral sequence theory.  In this short note, we present a simple proof for the theorem of  Nagel and Schenzel.